2014
DOI: 10.1007/s00220-014-1976-2
|View full text |Cite
|
Sign up to set email alerts
|

Scalar Product of Bethe Vectors from Functional Equations

Abstract: In this work the scalar product of Bethe vectors for the six-vertex model is studied by means of functional equations. The scalar products are shown to obey a system of functional equations originated from the Yang-Baxter algebra and its solution is given as a multiple contour integral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…Scalar products of Bethe vectors can also be tackled through the algebraic-functional method. This was demonstrated in [Gal14] for the six-vertex model with boundary twists, and in [Gal15] for the case of open boundaries. In particular, in the works [Gal14,Gal15] we have obtained a system of two functional equations determining such off-shell scalar products.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Scalar products of Bethe vectors can also be tackled through the algebraic-functional method. This was demonstrated in [Gal14] for the six-vertex model with boundary twists, and in [Gal15] for the case of open boundaries. In particular, in the works [Gal14,Gal15] we have obtained a system of two functional equations determining such off-shell scalar products.…”
Section: Introductionmentioning
confidence: 80%
“…In the work [Gal14] we have presented functional equations determining the scalar product (2.7). Among the results of [Gal14] we have also shown that the specialization (2.9) satisfy a simpler functional relation exhibiting the same structure as the equation satisfied by the partition function of the six-vertex model with domain-wall boundaries [Gal13b,Gal13a]. This simplified equation has also been studied in [GL15] and it is given as follows.…”
Section: Bethe Vectors and Scalar Productsmentioning
confidence: 99%
“…To date all cases in which the functional method has been used to obtained a closed expression were previously tackled using the Korepin-Izergin method. For the six-vertex model the domainwall partition function [8,32] was of course first found by Korepin and Izergin [23,24,28], the reflecting-end partition function [20] by Tsuchiya [43], and the corresponding (off-/on-shell) scalar products of Bethe vectors [13,14] by Slavnov [40], Wang [44] and Kitanine et al [25]. In the dynamical (sos) case the domain-wall partition function [10,12] was found by Rosengren [38], and the reflecting-end partition function [31,32] by Filali and Kitanine [4,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…[40], via the functional method [13,14]. On the other hand, for the domain-wall partition function of the Izergin-Korepin nineteen-vertex model, which was computed exactly at a particular root of unity [21], ingredient (ii b ) seems to fail because the analogue of (3.4) mixes the two creation operators B 1 and B 2 for that model.…”
Section: Further Examples 41 Comments On Applicabilitymentioning
confidence: 99%
See 1 more Smart Citation